2017
DOI: 10.1212/wnl.0000000000004086
|View full text |Cite
|
Sign up to set email alerts
|

Structural MRI markers of brain aging early after ischemic stroke

Abstract: Objective:To examine associations between ischemic stroke, vascular risk factors, and MRI markers of brain aging.Methods:Eighty-one patients (mean age 67.5 ± 13.1 years, 31 left-sided, 61 men) with confirmed first-ever (n = 66) or recurrent (n = 15) ischemic stroke underwent 3T MRI scanning within 6 weeks of symptom onset (mean 26 ± 9 days). Age-matched controls (n = 40) completed identical testing. Multivariate regression analyses examined associations between group membership and MRI markers of brain aging (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 43 publications
(52 reference statements)
6
48
0
Order By: Relevance
“…The proposal that stroke is specifically associated with accelerated brain aging prior and after stroke has been made by several authors. Neuroimaging markers of brain aging, such as smaller hippocampal and total brain volumes, and increased white matter hyperintensity load, have been linked to both, vascular brain injury prior to the stroke event (Seshadri et al, 2004;Knopman and Hooshmand, 2017;Werden et al, 2017) and continued brain atrophy and neurodegeneration (Knopman et al, 2009;Kooi Ong et al, 2017). For acute stroke, it has been estimated that during stroke or transient ischemeic attack (TIA), compared with the normal rate of neuronal loss in brain aging, the ischemic brain ages 3.6 years each hour without treatment (Saver, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The proposal that stroke is specifically associated with accelerated brain aging prior and after stroke has been made by several authors. Neuroimaging markers of brain aging, such as smaller hippocampal and total brain volumes, and increased white matter hyperintensity load, have been linked to both, vascular brain injury prior to the stroke event (Seshadri et al, 2004;Knopman and Hooshmand, 2017;Werden et al, 2017) and continued brain atrophy and neurodegeneration (Knopman et al, 2009;Kooi Ong et al, 2017). For acute stroke, it has been estimated that during stroke or transient ischemeic attack (TIA), compared with the normal rate of neuronal loss in brain aging, the ischemic brain ages 3.6 years each hour without treatment (Saver, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, many studies have demonstrated a relationship between neurodegeneration and cerebrovascular disease (CVD). For instance, Werden and colleagues [12] found lower hippocampal volumes among first-ever and recurrent stroke patients. Post-stroke victims also had significantly lower ipsilateral hippocampal volume than healthy controls [13].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the increasing evidence that brain changes are seen prior to visible cerebrovascular injury on fluid‐attenuated inversion recovery (FLAIR; ie, WMH and macroscopic infarctions7, 8, 9, we focused on MRI measures that captured brain health and did not include FLAIR findings.…”
mentioning
confidence: 99%
“…[3][4][5][6] Recent work has also shown that these changes precede the appearance of overt brain lesions. 7,8 The inability to quantify the effect of systemic vascular health on early brain structural and functional changes in a meaningful View this article online at wileyonlinelibrary.com.…”
mentioning
confidence: 99%